2005
DOI: 10.1007/s00213-005-0158-5
|View full text |Cite
|
Sign up to set email alerts
|

Striatal dopamine transporter availability with [123I]β-CIT SPECT is unrelated to gender or menstrual cycle

Abstract: These findings suggest that in using DAT or SERT ligands in the study of neuropsychiatric disorders, matching of female subjects according to a menstrual cycle phase is unnecessary. Although the present investigation did not confirm previous reports of gender differences in striatal DAT availability, controlling for gender in such studies still seems advisable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 56 publications
2
20
2
Order By: Relevance
“…However, although all subjects evidenced a luteal-phase rise in progesterone, 4 subjects did not have luteal-phase progesterone levels greater than 3 ng/mL, suggesting an anovulatory cycle as occurs in as many as 38% of cycles in young women (27) and is consistent with other studies (28). Results did not differ when these subjects were eliminated from the analyses.…”
Section: Study 2: the Effect Of Menstrual Cyclesupporting
confidence: 86%
See 1 more Smart Citation
“…However, although all subjects evidenced a luteal-phase rise in progesterone, 4 subjects did not have luteal-phase progesterone levels greater than 3 ng/mL, suggesting an anovulatory cycle as occurs in as many as 38% of cycles in young women (27) and is consistent with other studies (28). Results did not differ when these subjects were eliminated from the analyses.…”
Section: Study 2: the Effect Of Menstrual Cyclesupporting
confidence: 86%
“…The influence of menstrual phase and sexsteroid hormones on other neurotransmitter and receptor systems has been underresearched. Striatal dopamine transporters do not vary with menstrual cycle phase (28), and there is conflicting evidence on variations in dopamine D 2 receptors by phase of cycle (49,50). Serotonin transporter availability also does not fluctuate (28), whereas the serotonin 2A receptor (51) may fluctuate with menstrual cycle phase.…”
Section: The Effect Of Menstrual Cycle Phase On B 2 -Nachr Availabilitymentioning
confidence: 99%
“…Several studies have reported a similar effect of sex on DAT, with females showing greater DAT uptake than males (24,28). However, other studies could not confirm this association (29). We did not find any association between striatal DAT availability and age, an established factor of influence (24).…”
Section: Discussioncontrasting
confidence: 61%
“…Replacement of testosterone in castrated male rats increases SERT mRNA and SERT availability [37]. Since we did not measure sex hormones, and Best et al [38] found no relationship between menstrual cycle or sex hormones and SERT availability in healthy individuals, these explanations remain speculative and should be examined further.…”
Section: Methodological Explanations For Inconsistent Findingsmentioning
confidence: 84%